2022
DOI: 10.36129/jog.2021.07
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting childbearing decision making among Iranian couples: a qualitative study

Abstract: Objective. Childbearing decision-making is a complex process involving many social, economic, political, and individual factors. This study aimed to identify effective factors on the childbearing intention among Iranian couples. Patients and Methods. This qualitative study was conducted on 15 Iranian couples using a conventional content analysis during 2017-2018. The data was collected using in-depth, semi-structured, individual interviews and analyzed in five steps using the Graneheim and Lundman ( 2004) appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Khedmat et al. ( 2022 ) explained the following four categories as more effective on childbearing in Iran: couple's capability, parenting attitudes (paternal and maternal feelings, emotional support, social support, and age role), couple's interactions (satisfactory relationships, collaboration, and cooperation), and childbearing experiences. They indicated that most couples believed that couple's satisfactory relationships affected their childbearing intention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Khedmat et al. ( 2022 ) explained the following four categories as more effective on childbearing in Iran: couple's capability, parenting attitudes (paternal and maternal feelings, emotional support, social support, and age role), couple's interactions (satisfactory relationships, collaboration, and cooperation), and childbearing experiences. They indicated that most couples believed that couple's satisfactory relationships affected their childbearing intention.…”
Section: Discussionmentioning
confidence: 99%
“…Khedmat et al. ( 2022 ) mentioned couple's interactions (satisfactory relationships, collaboration, and cooperation) as an important category for childbearing in Iran; in other words, family health has a key role.…”
Section: Introductionmentioning
confidence: 99%
“…As a developing nation, Iran has also experienced a rapid decline in fertility over the past decade [ 8 ]. The fertility rate in Iran has similarly dwindled in recent years, reaching 1.9 between 1978 and 2015 [ 9 ]. Confronted with this dwindling population growth, the Iranian government initiated incentivizing policies in 2012.…”
Section: Introductionmentioning
confidence: 99%
“…It could be argued that the desire for fertility in Iran is deeply intertwined with tradition, gender roles, and religious sentiments. The factors that underpin the desire for childbearing within families can ultimately lead to demographic shifts at the national level over time [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a developing nation, Iran has also experienced a rapid decline in fertility over the past decade (8). The fertility rate in Iran has similarly dwindled in recent years, reaching 1.9 between 1978 and 2015 (9). Confronted with this dwindling population growth, the Iranian government initiated incentivizing policies in 2012.…”
Section: Introductionmentioning
confidence: 99%